Penggunaan Gawai Dengan Kemampuan Daya Lihat Pada Anak Remaja SMA 1 Seteluk Didesa Seteluk Kabupaten Sumbawa Barat - Adawiyah, Robiatul; Putra, Ageng Abdi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Gadgets were created to facilitate communication and rapid developments, despite that the use of gadgets has also negative impacts such as eye disorders, sleep disturbances, and nerve disorders. Therefore, a related study has been conducted at SMAN 1 Seteluk using a non-experimental quantitative method with a cross-sectional research approach involving 450 student respondents. The study concluded that the use of gadgets among students in grades X and XI at SMAN 1 Seteluk tends to be infrequent, with an average usage duration of about 3-4 hours per day. The majority of students have normal visual acuity (6/6 - 6/7.5). There is a significant relationship between gadget usage and visual acuity among teenage students at SMAN 1 Seteluk based on the results of the Spearman Rank test.